4QInstruction : sagesse et eschatologie - Rey, Jean-Sébastien. (Studies on the Texts of the Desert of Judah, 2009)
This volume consists of an edition, a translation and a commentary of the most important fragments of 4QInstruction. Initially it deals with the linguistic characteristics of the scroll highlighting the links between 4QInstruction and Ben Sira, and also with the Community Rule and the Hodayot. It then investigates the Sapiential fragments dealing with poverty, husband-wife and parent-child relationships. Finally it examines the eschatological fragments. The work seeks to improve the edition and understanding of this fundamental text enhancing our knowledge of the history and development of thinking at Qumran. Moreover, it examines links which 4QInstruction establishes between purely Sapiential discourse and descriptions of eschatological judgement. This study substantially illuminates our understanding of the Wisdom movement in the early intertestamental period.